Boosting Construction Employees’ Performance Through Smart Ergonomic Moves - Mustapha Zakari; Boahene Akomah Benjamin; Kobina Aidoo Peter; Kurbom Tieru Chris (Baltic Journal of Real Estate Economics and Construction Management, 2023)
Musculoskeletal disorders (MSDs) are construction workers’ most prevalent occupational diseases due to awkward body posture, high repetition of work and vibration. The study sought to examine the different types of ergonomic moves that could improve construction workers’ performance. Findings show that majority of the workers were males and their trade groups cut across different trade groups (masonry, carpentry, plumbing, and electricals). There was a scarcity of civil engineers and quantity surveyors in almost all the construction firms. The most influential factors that contributed to musculoskeletal injuries among construction workers were extreme temperature, static posture and exertion of force at work. These factors have contributed to the loss of concentration and absenteeism at work, which have also led to delays in the execution of work. Further findings show that engineering control measures should be employed, and training and education should also be given to workers to prevent MSDs among employees to enable them to work smarter but not harder to improve their performance. Employers should include education and specific task training in the company’s policy for all newly employed personnel. Workers should also be monitored to ensure that they take a recess during the day’s work.